Bilateral Pseudomonas aeruginosa endophthalmitis following bilateral simultaneous cataract surgery - Kashkouli, MohsenBahmani; Salimi, Shabnam; Aghaee, Hossein; Naseripour, Masood (Indian journal of ophthalmology, 2007)
A bilateral simultaneous cataract surgery (BSCS) was performed on a 67-year-old man. The surgeon had not changed the surgical settings in between the two procedures for the two eyes. The patient developed fulminant bilateral endophthalmitis a day following the BSCS. Intravitreal culture grew Pseudomonas aeruginosa . The source of infection was not found. Immediate bilateral vitrectomy and intravitreal, subconjunctival, topical and systemic antibiotic did not save the eyes. Patient ended up with bilateral visual loss.